G342(P) Watch batteries – how many can you have?. (27th April 2016) - Khan, B; Khattak, J; Gupta, C; Mudgal, R
Abstract : Aims: A case study demonstrating the management of ingestion of multiple watch batteries and developments in management. Method: A case study of ingestion of multiple Lithium ion watch batteries by a 2 year old. The case was of an unusual nature as there were roughly 20 watch batteries ingested. Results: An initial abdominal x ray showed pooling of the batteries at the pylorus. He was managed conservatively, with laxatives after discussing with the surgical team at the tertiary care centre. He attended the next day with vomiting and malena. A repeat x ray showed the batteries widespread- some at the pylorus and some in the small intestine. He was then assessed by the surgeons, an Oesophagogastrodeudenoscopy showed gastritis but no batteries in the stomach. Further, fluoroscopy showed all batteries gone past the pylorus. A subsequent post discharge x ray confirmed only two batteries remaining, which the child passed in due course as well. According to current evidence available on toxbase and National Battery Ingestion Hotline (US), patients with batteries seen within the esophagues should have the batteries removed immediately because of the risk of corrosive damage or perforation. Patients with batteries seen in the stomach should be reviewed at 48 h. Failure of large diameter battery (>20 mm) to pass through the pylorus within 48 h or signs of leakage or bleeding requires removal of the battery. If the battery has passed through the pylorus and the patient is asymptomatic, no further observations are required. The patient or guardian should be asked to observe stools to ensure passage of the battery up to two weeks, and a radiograph can be considered if batteries not seen in stools by then. The use of laxatives is not recommended. Conclusion: Battery ingestion can be challenging to manage, especially when multiple batteries are ingested. Close observation is required in such cases.